Wunderhorn songs : Fourteen songs to texts from youth's magic horn for voice and piano" - MAHLER, Gustav (G. Schirmer. Inc., 1968)
Der schildwache nachtlied : Sentinel's night songnVerlome muh : All in vainnTrost im ungluck : Comfort in sorrownWer hat dies liedlein erdacht? : Who thought of this song?nDas irdische leben : Earthly life